HOLOCAUST, GOD AND THE 'RAT LINES' OF PHILOSOPHY - Soldat, Oleg (Politeia, 2023)
The subject of this paper concerns two mechanisms wich help philosophy to circumvente the subject of Holocaust. These are: the philosophy of Heidegger and the neo-marxists tenets of so called Frankfurt School, especially those of Theodor Adorno. While Heidegger is seen in this paper as a resulting prioritization of chtonic symbolism within the the culture of Wiemar Germany, which pushes out the alternative of Ernst Cassirer, the leftist matrix of Adorno’s thought is equally seen as a distancing paradigm that abolishes Biblical language, through metaphysics. Paper investigates in some details these mechanisms which aim at abolishing strategic solutions of both Jewish nation and Holocaust – in the package of Zionist ideals. Author sees philosophical fixation on generic trajectoria of man-as-species, as a way of devious handling of the specifics of the Jewish existence.
Keywords: Aby Warburg; symbolism; Ernst Cassirer; ascending and descending; sign; Davos; Holocaust